Pollen morphology of Scorzonera s.l. (Asteraceae, Cichorieae, Scorzonerinae) occurring in Iran - Ebrahimi, Atefeh; Attar, Farideh; Nazemiyeh, Hossein; Mirtadzadini, Mansour; Blackmore, Stephen (Phytotaxa, 2023)
Pollen characters of 48 species of Scorzonera s.l. distributed in Iran were investigated by using light and scanning electron microscopy. The pollen grains are isopolar, radially symmetric, generally 3-zonocolporate, rarely 2-colpororate or 4-colporate. The pollen grains are oblate-spheroidal in shape (P/E=0.89 to 0.99) with the polar axes 37.1–58.1 µm and the equatorial axes 38.8–60.6 µm. We adopted the four pollen types recognized by Blackmore based on the number and position of their lacunae. For the first time, some pollen grains of S. longipapposa and S. tortuosissima were shown to have 26 (24+2) lacunae. We compared pollen morphological characters with the findings of the most recent systematic treatment. Type A with 6 lacunae was observed in Takhtajaniantha pusilla and S. parviflora, type B with 18 lacunae in Gelasia, type C with 20 lacunae in Pseudopodospermum and type D with 24 lacunae in Ramaliella, S. renzii and the Podospermum clade (except S. laciniata) in Scorzonera. We also observed 15 or 18 lacunae in S. rupicola. The pollen in Scorzonera appears to evolve toward reduction of spines in S. parviflora, extension of spines in the Podospermum clade, enlargement of the space between ridges and increase in the number of lacunae (S. longipapposa and S. tortuosissima). 26 pollen characters of the examined species were analysed by UPGMA and PCA. Pollen size, spine size, distance between spines, number and arrangement of spines between two equatorail lacunae, exine thickness, spine length/P or E, dimensions of lacunae and polar area were shown to contribute significantly to understanding the morphology of Scorzonera.